Size-aependent arsenic accumulation in Scrobicularia plana in a temperate coastal lagoon (Ria de Aveiro, Portugal) - Ereira, T.
Sediment, suspended particulate matter (SPM), water and clam Scrobicularia plana samples were collected in a temperate coastal lagoon with anthropogenic impact. Arsenic levels in sediments, SPM and water presented a spatial concentration gradient. A significant linear regression between arsenic levels in S. plana and SPM suggests particulate matter as the main route of arsenic exposure. Trend analysis showed that total arsenic concentrations in S. plana generally increased with size class, reflecting lifespan bioaccumulation. Despite being efficient in reflecting environmental contamination levels, results suggest that arsenic accumulation by S. plana may not be a passive process, given the proportionally lower accumulation in high contamination areas. Annual bioaccumulation rates ranged from 5.6 to 1 mg kg−1 year−1, suggesting a possible toxicity risk for individuals of the most contaminated area. Despite the absence of regulatory guidelines, food safety assessment highlighted possible adverse effects of consuming S. plana in most contaminated areas.